2022
DOI: 10.1155/2022/2481071
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Inflammatory-Associated Gene Signature and Immune Infiltration Patterns in Intervertebral Disc Degeneration

Abstract: Background. Both inflammatory factors and immune response play important roles in the pathogenesis of intervertebral disc degeneration (IDD). However, a comprehensive analysis of interaction between inflammatory response-associated genes (IRGs) and immune microenvironment in patients with IDD remains lacking. Hence, the current research is aimed at investigating the correlations between IRG signatures and immune cells in the progression of IDD. Methods. The expression profiles (GSE27494 and GSE41883) and IRGs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The findings demonstrated that whereas eosinophils and Th2 cells reduced in the deteriorated nucleus pulposus compared to the normal group, the number of macrophages, CD8T cells, dendritic cells, and Th17 cells rose. The importance of macrophage infiltration in the etiology of IDD has been validated by recent research (Lan et al, 2022;Yan et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…The findings demonstrated that whereas eosinophils and Th2 cells reduced in the deteriorated nucleus pulposus compared to the normal group, the number of macrophages, CD8T cells, dendritic cells, and Th17 cells rose. The importance of macrophage infiltration in the etiology of IDD has been validated by recent research (Lan et al, 2022;Yan et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Zhang et al identified inflammatory response-related features using WGCNA and LASSO, and explored the relationships between them and immune infiltration in IVDD. In addition, IL-1β, LYN, and NAMPT were validated as possible biomarkers [ 28 ]. Zhu et al constructed good genetic and lncRNA diagnostic models by systematic analysis of lncRNA and microRNA expression profiles and lncRNA and miRNA expression between IVDD and healthy patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have attempted to explore the underlying mechanisms of IDD by bioinformatic analysis, including inflammatory response, immune infiltration, mitochondrial dysfunction, etc ( 53 , 54 ). The present study focused on the association between ferroptosis with IDD, and provided novel insights into the pathogenesis of IDD.…”
Section: Discussionmentioning
confidence: 99%